An improved immune algorithm for simple assembly line balancing problem of type 1. Issue 4 (December 2017) - Zhang, Han-ye
In order to solve the simple assembly line balancing problem of type 1, an improved immune algorithm is proposed. Compared with the basic immune algorithm: (1) The similarity formula between any two antibodies is simplified in the improved immune algorithm. (2) Introducing immune adjustment, vaccine extraction, vaccination, and immune selection, the improved immune algorithm prevents population degradation. The validity of the proposed improved immune algorithm is tested by means of two computational examples with reference instances, and the results show that the proposed improved immune algorithm is an efficient approach to solve the simple assembly line balancing problem of type 1.